Cloud Computing and Artificial Intelligence for Secure and Sustainable Digital Transformation - Andayani, Dwi; Lestari Santoso, Nuke Puji; Hua, Chua Toh; Henry, Bintang Nandana (ADI Journal on Recent Innovation (AJRI), 2026)
The rapid growth of cloud computing and Artificial Intelligence (AI) has accel- erated digital transformation in business organizations while increasing concerns related to data security and sustainability. Ensuring secure and sustainable digital transformation has therefore become a strategic priority in the current digital economy. This study aims to examine the role of cloud computing and AI in supporting secure and sustainable digital transformation in business operations. This research adopts a quantitative approach by collecting survey data from 300 organizations that have implemented cloud computing and AI technologies. The data are analyzed using Structural Equation Modeling (SEM) to evaluate the relationships between cloud computing adoption AI capability digital security and sustainability performance. The results show that cloud computing adoption has a significant positive effect on secure digital transformation. AI capability also significantly enhances digital security and operational sustainability. Furthermore the integration of cloud computing and AI strengthens organizational readiness for sustainable digital transformation. The findings indicate that organizations leveraging both cloud computing and AI achieve higher levels of digital security and sustainability compared to those adopting these technologies independently. This study provides empirical evidence that integrated cloud and AI strategies are essential for achieving secure and sustainable digital transformation and offers practical implications for managers and policymakers in designing technology driven business strategies.